Innovative consumer behaviour towards sports wear - SANKAR, DR. JEGANATHAN GOMATHI; MR. RISHIKESH. R (The journal of contemporary issues in business and government, 2020)
The research paper titled the consumer behaviour towards sportswear. The objective of the study is to analyze the consumer behaviour towards sportswear. Descriptive research is used in the study as the research design and the sampling method used is convenience sampling. The sample size of the study is 90 respondents and it is analyzed using SPSS tool. The collected data were classified, tabulated and analyzed with statistical tools such as frequency analysis, T-test, Mean analysis and ANOVA test. It is found that factor affecting consumer preference, brand preference, price, quality and comfort on sports products.